Most marathon runners at the 2017 IAAF World Championships were rearfoot strikers, and most did not change footstrike pattern - Hanley, B.; Bissas, A.; Merlino, S.; Gruber, A. H. (Journal of Biomechanics, 2019)
The aim of this study was to analyze footstrike patterns in elite marathon runners at the 2017 IAAF World Championships. Seventy-one men and 78 women were analyzed in their respective races. Athletes` footstrike patterns were recorded (120 Hz) at approximately 8.5, 19, 29.5 and 40 km ("Laps 1 - 4") and categorized as either rearfoot (RFS), midfoot or forefoot striking; the latter two were classified together as non-rearfoot striking (NRFS). The most common footstrike pattern was RFS, with proportions never less than 54% of men or 67% of women at any distance. There were no sex-based differences for proportion of footstrike patterns, and there were no differences between footstrike proportions when comparing the top and bottom 50% of men finishers, or between women during Laps 1 and 2. A greater proportion of the top 50% of women maintained NRFS than amongst the bottom 50%. The proportion of RFS increased with distance run in the men`s race, although more than 75% of athletes across both marathons had consistent footstrike patterns between laps (79 RFS and 36 NRFS). As most athletes were RFS (including the top four finishing men), there appears to be no clear advantage to NRFS in marathon running. Coaches should note that it is normal for elite marathon runners to be either RFS or NRFS; however, forefoot striking was rare. The high proportion of athletes who maintained their footstrike pattern reflected individualized preferences for a given footstrike pattern.